An Estimation Method for Marginal Cost of Distribution System Reliability based on Consumer-Centric Reliability Assessment. (February 2019) - Liu, Liyang; Wang, Shouxiang; Huang, Renle
Abstract: Traditional estimation methods for marginal cost of distribution system are based on traditional reliability assessment method and metrics. However, traditional reliability assessment methods mainly focus on electricity outages observed from the system side, regardless of whether end consumers are in need of electricity during such outage events. That is, they may not truly reflect actual impacts of various outages on consumers with different power demand during the outage time, and the cost estimation based on them may not truly reflect the exact marginal cost of distribution system reliability sensed from consumers. To overcome this deficiency, a new method based on Consumer-Centric Reliability Assessment (CCRA) to estimate the Marginal Cost of Distribution System Reliability (MCDSR) is proposed in this paper. Several new indices are proposed to quantitatively evaluate MCDSR sensed by consumers. Two marginal cost curves for two reliability metrics are deduced to describe the relationship between reliability level and marginal cost, considering actual interruption time of outages, consumers' power consumption features and load demand (represented by load curve) during outage events. The IEEE-RBTS distribution system is studied to illustrate the effectiveness and efficiency of the proposed indices and estimation methods.